The teaching of reading comprehension and metacomprehension strategies. A program implemented by teaching staff - Madariaga Orbea, José María; Martínez Villabeitia, Estibaliz (Anales de Psicología / Annals of Psychology, 2010)
This paper presents a piece of research in which a program for the direct teaching of reading comprehension and metacomprehension strategies addressed to a sample of Second Cycle Primary Education stu-dents was drawn up. A series of meetings were held with the teachers of the target sample students in order to train them on how to apply the program. This training had the purpose of making the program applica-tion in the classroom more natural and of providing further awareness for its practice in the future. It was 457 pupils of a Spanish speaking town of Vizcaya enrolled in school in Spanish and Euskera. The results support the hypothesis that a significant improvement of reading comprehension in both languages is achieved through the program, and that the effect of some attitudinal variables is minimised. The evaluation carried out by the participants showed that their motivation and the program’s implementa-tion were satisfactory.